Anti-Factor Xa Levels in Low-weight Surgical Patients Receiving Enoxaparin for Venous Thromboembolism Prophylaxis: A Prospective Cohort Study. (19th June 2020) - Hakeam, Hakeam A.; Al Duhailib, Zainab; Alsemari, Muhannad; Alwaibah, Reem M.; Al Shannan, Madhawi F.; Shalhoub, Munirah
Enoxaparin is indicated for thromboprophylaxis in non-orthopedic surgical patients at a fixed dose of 40 mg daily. According to the US Food and Drug Administration's enoxaparin prescribing information, this dose exposes low-weight patients (males < 57 kg, females < 45 kg) to a higher risk of bleeding. This study aimed to determine the rate of achieving a prophylactic peak anti-factor Xa (AFXa) level in low-weight surgical patients using enoxaparin 30 mg daily. Low-weight patients admitted for abdominopelvic or noncardiac thoracic surgery from May 2018 to May 2019 were prospectively studied. After receiving daily enoxaparin 30 mg, peak AFXa levels were assessed for achieving a prophylactic level (0.2-0.5 IU/mL). In 121 patients, the proportion of achieving a prophylactic peak AFXa level was 66.1%. More females (84.8%) achieved a prophylactic level compared to males (54.7%, P = .001). All out-of-range peak AFXa levels (33.9%) were sub-prophylactic. The median peak AFXa level was lower in males (0.24 [0.1-0.47] IU/mL) than females (0.31 [0.1-0.5] IU/mL; P < .001). On univariate analysis, female sex and weight were associated with achieving a prophylactic peak AFXa level. On multivariate analysis, only female sex was independently associated with an adequate prophylactic AFXa level (odds ratio 3.17, 95% CI: 1.32-11.94; P = .014). Four venous thromboembolism events (3.3%) were observed in patients with sub-prophylactic peak AFXa levels (9.7%). Two-thirds of low-weight surgical patients achieved a prophylactic peak AFXa level using daily enoxaparin 30 mg. This dose is likely to provide adequate thromboprophylaxis in low-weight females.